A Combinatorial proof of a partition identity of Andrews and Stanley - Andrew V. Sills (International Journal of Mathematics and Mathematical Sciences)
In his paper, On a partition function of Richard Stanley, George Andrews proves a certain partition identity analytically and asks for a combinatorial proof.This paper provides the requested combinatorial proof.